2020
DOI: 10.3748/wjg.v26.i42.6582
|View full text |Cite
|
Sign up to set email alerts
|

Vascular anomalies associated with hepatic shunting

Abstract: Congenital vascular anomalies affecting the liver have been described in the scientific literature for decades. Understanding these malformations begins with knowledge of hepatic vascular embryology. Surgeons have applied numerous classification systems to describe both intrahepatic and extrahepatic shunts, which can confuse the reader and clinician. In our experience, focusing on one classification system for extrahepatic shunts and one for intrahepatic shunts is better. Today many patients with these shunts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
(26 reference statements)
0
11
0
Order By: Relevance
“… 11 Large or multiple hepatic hemangiomas can have an increased risk of high vascular flow resulting in hemodynamic instability and heart failure. 12 Pulmonary hypertension in neonates can be associated with congenital portosystemic shunts. The pathophysiology is incompletely understood, but it is thought to be secondary to fluid overload as well as a lack of hepatic clearance of vasoactive substances.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 11 Large or multiple hepatic hemangiomas can have an increased risk of high vascular flow resulting in hemodynamic instability and heart failure. 12 Pulmonary hypertension in neonates can be associated with congenital portosystemic shunts. The pathophysiology is incompletely understood, but it is thought to be secondary to fluid overload as well as a lack of hepatic clearance of vasoactive substances.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology is incompletely understood, but it is thought to be secondary to fluid overload as well as a lack of hepatic clearance of vasoactive substances. 12 In some patients with CPSS, shunt closure or liver transplantation may prevent the progression of pulmonary hypertension. 13 Hepatic tumors can develop from altered hemodynamics secondary to insufficient portal vein perfusion and compensatory increased hepatic arterial flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Georghiou et al successfully cured pulmonary arteriovenous malformation by lobectomy ( 14 ). A recent report suggested that partial liver resection is also an option for large intrahepatic shunts that do not close spontaneously ( 15 ). Petrovic et al reported a successful left lateral bisegmentectomy in a HHT patient with liver abscess ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Causes of increased hepatic arterial blood flow include HABR due to decreased portal blood flow and the presence of congenital or acquired shunt pathways [ e.g. , hepatic AP shunts), hepatic arterial–hepatic venous shunts (AV shunts)], hereditary hemorrhagic telangiectasia (Figure 2 ), hepatic trauma, and others[ 11 ].…”
Section: Causes Of Localized Intrahepatic Hemodynamic Alterationsmentioning
confidence: 99%